2018
DOI: 10.2174/1570163814666171017162730
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Nitric Oxide in Preterm Neonates with Refractory Hypoxemia Associated to Oligohydramnios

Abstract: iNO therapy can be useful in a subgroup of preterm infants with a high risk of death secondary to hypoxemia. Although this report is based on a small number of cases, it follows the directions of other studies that suggest that iNO therapy can benefit preterm neonates, particularly those exposed to oligohydramnios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Two died of hemorrhage in the lungs secondary to the ductus arteriosus, and the other died of pneumonia. Thus, iNO therapy is available for a subsection of high-risk episodes of prematurity due to hypoxemia, but not widely used [ 2 ]. Pan et al investigated the clinical efficacy of intratracheal infusion of pulmonary surfactant (PS) combined with budesonide in the prevention of bronchopulmonary dysplasia (BPD) in very low birth weight (VLBW) infants.…”
Section: Introductionmentioning
confidence: 99%
“…Two died of hemorrhage in the lungs secondary to the ductus arteriosus, and the other died of pneumonia. Thus, iNO therapy is available for a subsection of high-risk episodes of prematurity due to hypoxemia, but not widely used [ 2 ]. Pan et al investigated the clinical efficacy of intratracheal infusion of pulmonary surfactant (PS) combined with budesonide in the prevention of bronchopulmonary dysplasia (BPD) in very low birth weight (VLBW) infants.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] The first two studies were both small, with eight exposed infants in each, and they had a short follow-up period that only evaluated short-term mortality and an oxygenation index. 26,27 The third study reported that iNO did not improve either the survival or morbidity of children with lung hypoplasia. Our study did not find that iNO was advantageous for pPROM, compared to not using it.…”
Section: Discussionmentioning
confidence: 99%
“…25 This stated that iNO could be used for preterm in- As well as recommending iNO for neonates with PPHN, 25 a number of studies have also suggested that it could be used for infants with respiratory distress syndrome following pPROM, oligohydramnios and lung hypoplasia. [26][27][28] The first two studies were both small, with eight exposed infants in each, and they had a short follow-up period that only evaluated short-term mortality and an oxygenation index. 26,27 The third study reported that iNO did not improve either the survival or morbidity of children with lung hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale that iNO inhalation might benefit a subset of pre-term newborns was based on existing case reports and series. Initially, the investigated pre-term infants presented with PHTN and HRF associated with pre-term premature rupture of membranes (PPROM), as this was proposed to cause PHTN in term and pre-term newborns, possibly by chest compression or decreased distal airway pressure (103,(131)(132)(133)(134). However, the observation that iNO and effective ventilation management dramatically improve oxygenation in newborns with a short period of PPROM is not always consistent with the theory of severe lung hypoplasia.…”
Section: A Personalized Evaluation and Treatment Of Phtn In Pre-term mentioning
confidence: 99%